To explore the influence of AR-filtered selfies on impression management in users' intrapersonal communication under computer-mediated communication (CMC) - Zhang, Di; Alsagoff, Syed Agil; Yasin, Megat Al Imran; Razi, Siti Aishah Muhammad (RedFame Publishing, 2024)
Selfies are increasingly being shared on social media. On the basis of selfies, traditional beauty filters only finish tasks like whitening and face-lifting. However, with the introduction of augmented reality technology into selfie filters, more and more virtual impressions are presented, causing new influences on social media.This paper explores the influence of AR filters on the impressions management of selfie under Computer Mediad Communication (CMC) from the perspective of Goffman's (1959) dramaturgical theory. This study adopts a qualitative phenomenological research paradigm. Data were collected using document analysis, focus groups and in-depth interviews at two universities in Pingdingshan, China. Research has found that the media characteristics of AR filter selfies allow users to have a rich ability to choose and present their impressions, prompting users to project multiple impressions of themselves on social media. Let users be willing to communicate intrapersonally with AR selfies, thereby achieving self-improvement. This article expands the application scope of new media AR filters of dramaturgical theory in CMC. It also provides a basic understanding of the further communication influence of AR selfies on senders and receivers in CMC. This can provide relevant reference for the government to formulate media policies and manage social media platforms. It can also provide relevant research results as research by other relevant scholars.